CoffeeScript accelerated Javascript development - Burnham, Trevor (Pragmatic programmers, 2015)
This extensively revised and updated new edition includes an all-new project to demonstrate CoffeeScript in action, both in the browser and on a Node.js server. There's no faster way to learn to write a modern web application.